Gendered dynamics of Twitter engagement: An analysis of Colombian parliamentarians during electoral and non-electoral periods - Ferré-Pavia, Carme (2025)
This study investigates the gender dynamics in how Colombian members of Congress use Twitter during electoral and non-electoral periods. Using a quantitative analysis of 689,576 tweets collected in 2020 and 2022, the findings reveal nuanced differences in social media behaviour between male and female politicians. While male politicians generally have a larger follower base and higher retweet rates during non-electoral periods, these advantages diminish or even reverse during elections. Female politicians show relative gains in retweets and follower acquisition during electoral periods, suggesting that heightened competition and visibility create a more level playing field for engagement. Contrary to expectations, male politicians tweet more frequently overall, but female politicians increase their activity significantly during elections. These findings suggest that gender disparities in political communication on Twitter are not static but context-dependent, with electoral periods offering unique opportunities for female politicians to amplify their messages. While further research is needed to explore the role of content and audience behaviour, this study highlights the complex interplay of gender, visibility, and engagement in online political communication.